2018
DOI: 10.1088/1757-899x/288/1/012098
|View full text |Cite
|
Sign up to set email alerts
|

Designing Web Database Application for Local Medicinal Plants of Gorontalo Using MVC Architecture

Abstract: Abstract. There is a significant number of unpublished research by university lecturers and students about Gorontalo's local medicinal plants that have contributed to the insufficiency of information to the society regarding the benefits of local medicinal plants. Moreover, the public lacks digital backup and documentation of the medicinal plants referred. This research aims to create a web database of Gorontalo's local medicinal plant, by comprising waterfall method of software engineering approach. The water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…and Chen et al ., who showed that diversity in search fields enables users to find the needed information, while users are more dominant in search by scientific name of herbs and browsing by name, genus, species, and type. [ 8 16 ] In addition, another part of the findings showed that in the search options of the information system of medicinal plants, the option of browsing through the tree structure, authors or the creator, and the reference number was more important for the librarians. It may be judged that at the search phase, information literacy of users and their knowledge of how to select search keywords, formulate search strategies, and use capabilities are crucial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Chen et al ., who showed that diversity in search fields enables users to find the needed information, while users are more dominant in search by scientific name of herbs and browsing by name, genus, species, and type. [ 8 16 ] In addition, another part of the findings showed that in the search options of the information system of medicinal plants, the option of browsing through the tree structure, authors or the creator, and the reference number was more important for the librarians. It may be judged that at the search phase, information literacy of users and their knowledge of how to select search keywords, formulate search strategies, and use capabilities are crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In the research results by Latief et al ., Saini et al ., and Chowdhury also, various features of search results, including highlighting search terms, displaying keywords on the results page, and displaying retrieved documents as bibliographic information and abstract references, have been suggested to help users evaluate the search results. [ 8 9 28 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation